Tourism Development and Frequency of Nationalities in Kosovo Tourism - MILLAKU, Bedri; DRESHAJ, Adem; ELEZAJ, Elvis; KUQI, Bekë (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).10, 2021)
Tourism is one of the most important branches of society in many countries of the world. Today its development has taken an important impetus for the development of many societies which really accept tourism as a very important economic activity. Many places have changed the physiognomy of the landscape, giving importance to the development of this activity. It can rightly be said that many countries have received the epithet of developed countries because of the tourist destinations they have. In this way, the Republic of Kosovo, even though it is a young state, has at its disposal important potential values which really represent a tourist attraction. Although they are still in the process of developing and improving tourism which will be in function of the successful tourist offer. In order to develop successful tourism offers, potential values must be made available which will be used as a tourist attraction which is available for tourism development. And with this the overall economic development which affects the overall development of the country. The Republic of Kosovo has potential values which are useful for the development of the tourism product. This is best reflected around Rugova, respectively in Boge where we have a large frequency of different nationalities of tourists.